Profiling Metabolites through Chemometric Analysis in Orthosiphon aristatus Extracts as α-Glucosidase Inhibitory Activity and In Silico Molecular Docking - Faizal Maulana; Alfari Andiqa Muhammad; Ali Umar; Fachrur Rizal Mahendra; Muhammad Musthofa; Waras Nurcholis (Universitas Gadjah Mada, 2022)
Orthosiphon aristatus (called kumis kucing in Indonesia) is a valuable herb for diabetes mellitus treatment. In this study, LC-MS/MS and PCA analyses were used to investigate the metabolite profile, classify O. aristatus extracts, and assess the inhibitory activity of a-glucosidase and the probable bioactive compounds through in silico study. Results showed that the methanol and ethanol extracts of O. aristatus were active in α-glucosidase inhibitory activity. Both extracts contained 86 compounds as known from the LC-MS/MS analysis. PCA analysis identified 10 metabolites that correlated with α-glucosidase inhibitory activity. Results of in silico analysis obtained rosmarinic acid compound potentially act as anti-diabetic activity, which can be developed for further research.